SCHELER AND GHAZĀLĪ: EXPLORATIONS OF THE FINALITY OF KNOWLEDGE BETWEEN EAST AND WEST - Ms. Zora Hesova (Journal of Islamic Thought and Civilization, 2011)
The paper explores ways in which Islamic tradition in general, and Islamic philosophy in particular, contributes to a constructive rethinking of modernity in a dialogue between Western and Islamic thought. In modern Western thought, ethics and rational speculation came to be largely disconnected. Knowledge is conceived as instrumental to human empowerment and reduced to naturalised representation and information management. Ethics and values become problematic as ethical motivation could not be satisfactorily rationalised in the modern context. A series of European thinkers consider this disconnection as a major flaw of modern consciousness and address the question of modern moral wilderness. In Islamic philosophy, as well as in the pre-modern European tradition, on the other hand, knowledge has always had an ethical goal. Knowing and ethical becoming are indissociable. The moral dimension of knowledge is grounded in a specific anthropology, an epistemic concept of practical and experiential knowledge and a teleological frame of thought. After exposing the problem, the paper will concentrate on the ethical dimension of knowing as it is expressed in the work of Abu Hamid al-Ghazali. In third part it will look at the different ways in which modern Muslim thinkers from diverse backgrounds — Allama Iqbal, Mahdi Ha‘iri Yazdi, Seyyed Hossein Nasr and others — have sought to rehabilitate the traditional view of knowledge in modern terms. The paper will seek to characterise and analyse the multiplicity of approaches: metaphysical, analytical and traditionalist and show echoes of corresponding undertakings in Western philosophy.